Development of boost converter training kit as a practical tool in power electronics course - Junaidi Akbar; Krismadinata Krismadinata; Ahyanuardi Ahyanuardi; Asnil Asnil (Universitas Negeri Padang, 2021)
In the power electronics learning process, apart from theory, it is also necessary to carry out practicum learning to improve the competence of students, so that the learning process runs well, learning is held in the laboratory using a training kit. Practical training kit is very important in the educational process, especially at the level of vocational education at the diploma level. Its existence is very much needed to improve the competence of students and make it easier for teaching staff to carry out the teaching and learning process, especially for practicum activities. The aim of this research is to produce a boost converter practicum training kit, where the parameters are close to the values ​​calculated in theory and simulation. The method used is the experimental method in which the boost converter theory study is designed, made and tested. The test results show that the value of voltage, current and output power shows an average error presentation of less than 10% and the efficiency of the Boost Converter an average of 74% - 95%. The boost converter training kit can be produced well, so that it can be used as a support in power electronics practicum, especially on DC - DC Converter material.